2022
DOI: 10.3389/fmicb.2022.1035434
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity of Ganoderma (Ganodermataceae, Polyporales) with three new species and a key to Ganoderma in Yunnan Province, China

Abstract: Ganoderma is a globally distributed genus that encompasses species with forestry ecological, medicinal, economic, and cultural importance. Despite the importance of this fungus, the studies on the species diversity of Ganoderma in Yunnan Province, China (YPC) have poorly been carried out. During this study, opportunistic sampling was used to collect 21 specimens of Ganoderma from YPC. Morphology and multigene phylogeny of the internal transcribed spacer (ITS) regions, the large subunit of nuclear ribosomal RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Though the ITS gene can perform species division in the genus Ganoderma [ 20 , 21 ] and is the most abundant gene region in Ganodermataceae [ 45 ], depending on a single gene does not address all the problems in the classification of Ganoderma . For the complex groups in Ganoderma or the higher rank classification of Ganodermataceae , multigene phylogenetic analyses are essential [ 22 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though the ITS gene can perform species division in the genus Ganoderma [ 20 , 21 ] and is the most abundant gene region in Ganodermataceae [ 45 ], depending on a single gene does not address all the problems in the classification of Ganoderma . For the complex groups in Ganoderma or the higher rank classification of Ganodermataceae , multigene phylogenetic analyses are essential [ 22 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a sampling frequency of 100 generations was performed in the test. The burn-in fraction was set to 0.25 and posterior probabilities (PP) were determined from the remaining trees ( He et al, 2022 ). The consensus trees were plotted using FigTree v. 1.4.4 ( http://tree.bio.ed.ac.uk/software/figtree ; Rambaut, 2018 ) and edited using Adobe Illustrator CS 6.0 ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…(Mawar et al 2020;Morera et al 2021), Ficus sp. (Mawar et al 2020;He et al 2022), Mangifera indica (Foroutan and Jafary, 2007), Edy et al (2022) reported Persea americana to be a host tree to Ganoderma species. Persea americana, Albizia adianthifolia, and Mangifera indica were this study's most susceptible host trees.…”
Section: Ganoderma Weberianum (Bres and Henn)mentioning
confidence: 99%